Cigarette use among Arab Americans in the Detroit metropolitan area - Kulwicki, A. (1992)
Use of cigarette tobacco by large proportions of the population of Middle Eastern countries has been reported; however, little is known about smoking behavior in one of America's fastest growing minorities, the Arab Americans. The purpose of this study was to examine cigarette smoking behavior of 237 randomly selected Arab American adults from a telephone listing in the Detroit area. Participants lived in the geographic Arab American community and identified with a Middle Eastern cultural heritage. Nurses, who spoke both English and Arabic, interviewed one adult family member using the 59-item self-report from the Cardiovascular Risk Factor Survey developed by Rice. Mean age of respondents was 40.4 years, 97 percent had been born in the Middle East, and 67 percent had been living in the United States 15 years or less. Current smokers rate was 38.9 percent, former smokers rate was 11.1 percent, never smokers rate was 50 percent, and the quit ratio (proportion of ever smokers who are former smokers) was 22.2 percent. Fifty-four percent of the current smokers were between 25 and 34 years of age; fewer women than men were former smokers, and the highest proportion of current smokers were Lebanese. Subjects who had smoked for the longest time were the least well educated. Arab Americans in this sample had a higher smoking rate, a lower quitting rate, and a much lower quit ratio when compared with national and State of Michigan data. With the growing numbers of Middle Eastern immigrants, there is potential for a dramatic increase in smoking-related health problems.